WOMEN’S TIME, CINEMATIC TIME: PAST AND PRESENT IN THE FOUND FOOTAGE, OR COMPILATION FILM - MULVEY, Laura (Studia Universitatis Babeș-Bolyai Philologia, 2025)
Concepts of time are integral to the structuring of history and memory, often invisible, often implicit often seemingly following a teleological line between past and present. Recently, or even for some time now, the traditional image of temporality as linear has been challenged. Radical ideas of history have stretched the narrative causality of ‘then and then’. Perhaps particularly feminist history has associated the linear causal narrative with a patriarchal control of time, looking to find in women’s stories other patterns and configurations. On a different cultural level, memory necessarily blurs a mental image of time, dispersing the immediacy of a present ‘now’ with the dreaminess and uncertainty of a persistent ‘then’.